Insulin and Lispro Insulin: What is Common and Different in their Behavior? - M. Selivanova, Olga; Yu. Suvorina, Mariya; K. Surin, Alexey; V. Dovidchenko, Nikita; V. Galzitskaya, Oxana (Current Protein and Peptide Science, 2017)
There are different insulin analogues with various pharmacokinetic characteristics, such as, rapid-acting, long-acting, or intermediate-acting analogues. Since insulin tends to form amyloid aggregates, it is of particular interest to measure characteristic times of formation of amyloid aggregates and compare those to action times for insulin and its analogues. For the study we have chosen one of the insulin analogues - insulin Lispro, which is a fast acting insulin analog. It is usually thought of amyloid aggregation as a nucleation-dependent process. We have estimated the size of the primary nucleus to be one monomer and the size of the secondary nucleus to be around zero in both insulin and Lispro insulin aggregation processes. The main structural element of insulin and Lispro insulin amyloid fibrils is a rounded ring oligomer of about 6-7 nm in diameter, about 2-3 nm in height and about 2 nm in diameter of the hole. Fibrils of several μm in length are produced due to interaction of such oligomers. The packing of ring oligomers in fibrils differs because of the difference in their orderliness. Though the initial stages of fibril formation (monomer, oligomer) are similar, the further process depends on the unique sequence of each peptide. Namely the sequence affects the final morphology of mature amyloids. These observations allow us to conclude that formation of fibrils by short peptides occurs via and by means of oligomer ring structures. Such an important issue as the nature of polymorphism of insulin amyloid fibrils has been settled by us. The role of early oligomeric aggregates in such processes as nucleation and aggregation of amyloid fibrils has been examined.
Keywords: nucleus